Aldh1b1 expression defines progenitor cells in the adult pancreas and is required for Kras-induced pancreatic cancer - Mameishvili, Ekaterina; Serafimidis, Ioannis; Iwaszkiewicz, Sara; Lesche, Mathias; Reinhardt, Susanne; Boelicke, Nora; Buettner, Maren; Stellas, Dimitris; Papadimitropoulou, Adriana; Szabolcs, Matthias; Anastassiadis, Konstantinos; Dahl, Andreas; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
The presence of progenitor or stem cells in the adult pancreas and their potential involvement in homeostasis and cancer development remain unresolved issues. Here, we show that mouse centroacinar cells can be identified and isolated by virtue of the mitochondrial enzyme Aldh1b1 that they uniquely express. These cells are necessary and sufficient for the formation of self-renewing adult pancreatic organoids in an Aldh1b1-dependent manner. Aldh1b1-expressing centroacinar cells are largely quiescent, self-renew, and, as shown by genetic lineage tracing, contribute to all 3 pancreatic lineages in the adult organ under homeostatic conditions. Single-cell RNA sequencing analysis of these cells identified a progenitor cell population, established its molecular signature, and determined distinct differentiation pathways to early progenitors. A distinct feature of these progenitor cells is the preferential expression of small GTPases, including Kras, suggesting that they might be susceptible to Kras-driven oncogenic transformation. This finding and the overexpression of Aldh1b1 in human and mouse pancreatic cancers, driven by activated Kras, prompted us to examine the involvement of Aldh1b1 in oncogenesis. We demonstrated genetically that ablation of Aldh1b1 completely abrogates tumor development in a mouse model of KrasG12D-induced pancreatic cancer.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adult stem and progenitor cells; Aldehyde dehydrogenase; Organoids; Pancreatic ductal adenocarcinoma; Single-cell RNA sequencing